Manual dexterity and palmar grip strength of ipsilesional upper limb of post-stroke adults - Lopes, Alfredo (2020)
Stroke is the most common cause of long-term disability in adults and the motor impairment is the most common deficit. More than 80% of stroke patients experience acute motor dysfunction of the contralesional upper limb (UL), which becomes chronic for more than 40% of the patients